Potensi Getah Patikan Kebo (Euphorbia hirta L.) dalam Menurunkan Waktu Perdarahan pada Luka Kulit Tikus Putih (Rattus norvegicus) - Widya sriwarsih; Baiq Isti Hijriani; Siti Zaetun (Puslitbang Sekawan Institute Nusa Tenggara, 2023)
Indonesia has many types of plants that are abundant and can be used as medicine. One of the plants used as medicine is patikan kebo (Euphorbia hirta L.) because it contains of several chemical compounds, which are tannin, flavonoid and saponin. Tannin and flavonoid are the main compounds in plants that help to stop the bleeding. The purpose of this study was to determine the potential of patikan kebo’s latex (Euphorbia hirta L.) to decrease the bleeding time in skin wounds of white rats (Rattus norvegicus). This research is a pre experiment. The number of experimental animals used was 10 which were divided into 2 treatment groups (T1 and T2). The treatment group T1)was not dripped with patikan kebo’s latex (Euphorbia hirta L.) and treatment group T2 was dripped with patikan kebo’s latex (Euphorbia hirta L.) and then the bleeding time was measured. Based on result of Independent Sample T Test showed that P value = 0,006 (P<0,05), it means the bleeding time in skin wound of white rats that were dripped with patikan kebo’s latex and without dripped with patikan kebo’s latex are significant.